Prueba clínica de la secreción ácido gástrica: fines, expresión de los resultados, ejecución, complicaciones, significado de los resultados, utilidad. - CADILLO ALFARO, MARCO (2024)
This is a review of the clinical tests of gastric acid secretion. lt is emphasized its purpose, interpretation, how to do them, and clinical utility.